KEPENTINGAN INDIA BERGABUNG DENGAN SHANGHAI COOPERATION ORGANIZATION - Sembiring, Sulthan Saleh; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study discusses India's interests or needs to join the Shanghai Cooperation Organization. India and SCO have different views regarding a number of issues initiated by the organization. But India made the choice to join, India's choice to join the SCO was due to an interest. In this study the authors used qualitative methods using data sourced from books, journals, articles, mass media and official websites. The perspective used by the author is a realist perspective with foreign policy theory and the level of nation-state analysis. SCO is known as an organization dominated by Chinese influence which incidentally is a rival to India, but because of an interest India declared itself to join the organization. The results of this study show India's interest in joining the Shanghai Cooperation Organization due to economic cooperation, which is India's effort to increase trade with SCO countries, as well as to gain access to energy resources to drive India's industrial sector and is also influenced by regional security interests. Keywoards : National Interest, Regional Cooperation, Foreign Policy